AB1206 Can a Different Pattern of Radiographic Sacroiliitis Evaluation be Identified Using Eye-Gaze Traking?. (9th June 2015) - Ionescu, R.; Berghea, F.; Kosevoi-Tichie, A.; Saulescu, I.; Bojinca, V.; Groseanu, L.; Abobului, M.; Iorgoveanu, V.; Trandafir, M.; Duna, M.; Dobrin, M.; Neagu, A.; et al.
Abstract : Background: Assessment of sacroiliitis on radiograph is one of the most interpretable diagnosis radiologists and rheumatologists make. In an article published in 2002 1, A van Tubergen et al. approached the topic of training in assessing sacroiliitis on radiographs, if it improves the quality of diagnosis or not. The result was that neither individual training nor workshops improved performance. Eye-Gaze tracking devices collect information about the location and duration of eye fixation within a specific area on a computer monitor. R. Tai et al. 2 used the device to evaluate the behaviours of individuals as they solve standardized science assessment problems. Objectives: Identifying the differences in the assessment of sacroiliitis on radiographs, between senior and trainee doctors. Methods: This study included 11 participants (4 senior and 7 trainee doctors). All participants evaluated 13 pelvic region x-rays and assessed the presence of sacroiliitis and/or enthesitis. Evaluation time for each x-ray was 30 seconds, with a shorter time for senior doctors, if needed. On the 13 x-rays (2 were repeated), 6 areas of interest were established (sacroiliac joints (Sij), symphysis pubis (SP), femoral head down to the femoral neck (FH), the last two lumbar and the first sacral vertebrae). Eye movement of the participants was monitored using the Tribeye system. It evaluated the areas on which the participant was focusing, the order of evaluation and the time spent on each one. For analysis, SPSS v21 (IBM. Corp) was used. Results: Trainee doctors have spent an uneaven time in evaluating the two SIj (difference in absolute value=2.1sec (sd 1, 7)): the left SIj was appointed less time for evaluation. Also, there is a certain preference in the order of evaluation: the majority of participants evaluated the right SIj first. By comparison, the difference in evaluation time of the SIj by the senior doctors was only 0, 3sec (sd 1.2). The order of evaluation was also preferential for the right SIj. In evaluating enthesitis, trainee doctors pay less attention to the SP and the FH in comparison to the senior doctors (% of medium time spent on SP=7.4% by a trainee doctor vs. 12.8% for senior doctors (p<0.05), and 16.2% for both FH for trainee vs. 21.5% for senior doctors). No correlation between the stage of sacroiliitis and the time spent for evaluation of the SIj was found, regardless of the level of experience. Conclusions: Eye-Gaze Tracker analysis can determine the pattern of x-ray evaluation (in our study of sacroiliits evaluation); There is an asymmetry in the order of evaluation of the pelvic region images, regardless of the experience level. Trainee doctors spend less time in assessing certain areas of interest (sites of enthesitis) by comparison to the senior doctors. Thus, by identifying these areas with the help of Eye-Gaze Traker method, a feed-back is given in the education process. References: Radiographic Assessment of sacroiliitis by radiologists and rheumatologists: does training improve quality? A van Tubergen, et al., Ann Rheum Dis 2003; An exploration of the use of eye-gaze traking to study problem-solving on standardized science assessments, Robert H.Tai, et al., International Journal of Research and method in Education, Vo.l 29, No. 2, October 2006. Disclosure of Interest: None declared